Dental Students’ Perceptions before and after Attending a Centre for Children with Special Needs: A Qualitative Study on Situated Learning - Hani T. Fadel; Khlood Baghlaf; Afnan Ben Gassem; Hala Bakeer; Alla T. Alsharif; Saba Kassim (Dentistry Journal, 2020)
Objectives: To develop an in-depth understanding of the perceptions and experiences of senior dental students before and after fieldwork visits to a centre for children with special needs. Methods: A qualitative study utilised open-ended questions and involved 39 fifth-year dental students. A thematic analysis of the collected responses was undertaken, and a hierarchy of themes and subthemes were developed. Results: Analysis of the pre-visit responses revealed three main themes and a number of subthemes: ‘negative expectations’, ‘positive expectations’, and ‘pain expectations’. Similarly, four main themes with a number of subthemes emerged from the post-visit responses: ‘positive perceptions’, ‘negative perceptions’, ‘oral problems observed’, and ‘recommendations’. Conclusions: Within the study limits, different perspectives were extracted. Prior to the fieldwork visit, students expressed their lack of self-confidence and inadequate preparation. Following the situated learning visit experience, students’ perceptions of managing special needs children was positively influenced. Students were happy to be exposed to such an experience, but hoped for better organisation and specialised supervision in the future.